DAMPAK MEDIA SOSIAL TIKTOK TERHADAP MOTIVASI BELAJAR REMAJA DI KELURAHAN KADUMERAK KABUPATEN PANDEGLANG - Silvi Maulida; E. Nita Prianti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to determine the impact of TikTok social media on adolescents' learning motivation in Kadumerak Village, Pandeglang Regency, and to identify the efforts made to address that impact. This research employed a descriptive qualitative method. The research subjects consisted of 10 adolescents, 7 parents, 2 local community members and 1 representative of the village office. Data were collected through structured observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with data validity examined through source and technique triangulation. The results show that TikTok use has a dual impact, though negative tendencies are more dominant than positive ones. Adolescents experienced declining enthusiasm for learning, reduced concentration, and a habit of procrastinating on schoolwork due to high-intensity TikTok use, particularly at night. On the other hand, some adolescents also benefited from educational TikTok content that helped them understand difficult subjects. Efforts to reduce the negative impact included limiting usage duration, parental supervision, directing adolescents toward educational content, instilling religious and moral values, and involvement from community leaders and the village office, although a structured digital literacy program has yet to be implemented. This study concludes that TikTok social media has a significant impact on adolescents' learning motivation, with negative impacts being more dominant, so synergy among families, adolescents, the community, and the village government is needed to minimize this impact and optimize TikTok's positive potential as a learning medium.